Temporal changes in soil organic carbon and other near‐surface soil properties under native tallgrass prairie in the Arkansas River Valley - Katie Jansson; Kristofor R. Brye; Mike Richardson; Lisa S. Wood (Agrosystems, Geosciences & Environment, 2025)
Abstract One climate‐change mitigation pathway is soil carbon (C) sequestration. Native prairies have long been known for their soil C sequestration abilities, but the full extent of their sequestration capacity is not completely understood, particularly across diverse regions. This study evaluated the effects of soil depth and soil map unit‐prairie combination on changes in various soil properties from 2018 to 2022 in the top 20 cm of two native tallgrass prairies in west‐central Arkansas. Soil bulk density, pH, electrical conductivity, total nitrogen, total C (TC), soil organic matter (SOM), and Mehlich‐3 extractable soil nutrients were evaluated from the 0‐ to 10‐cm and 10‐ to 20‐cm depths in six soil map units across the two prairie ecosystems. Results indicated that soil pH was greater (p < 0.05) in 2022 than in 2018 in all six soil map unit‐prairie combinations, but remained acidic, averaging 5.1 in the top 10 cm. Soil organic matter was lower (p < 0.05) in 2022 than in 2018 in all soil depth–prairie combinations, ranging from −11.3 to 11.3 Mg ha−1 in the 0–10 cm of one combination to 3.3 Mg ha−1 in the 10‐ to 20‐cm depth of a different combination. Averaged across soil map unit‐prairie combination, soil TC was lower (p < 0.05) in 2022 than in 2018 in both soil depths. Results showed that soil C sequestration did not occur during the 4‐year study period, potentially meaning that the prairies have already reached an equilibrium soil C content and may not continue to sequester soil C indefinitely.